EVALUASI KADAR PATI TAHAN CERNA (PTC) DAN NILAI INDEKS GLIKEMIK MI SAGU (Evaluation of Enzymatically Resistant Starch and Glycemix Index of Sago Noodle) - Winda Haliza; Endang Y Purwani; Sri Yuliani (Jurnal Teknologi dan Industri Pangan, 2006)
This paper expressed the level of glycemic index and content of resistant starch of sago noodle. Determination of starch resistant of sago noodle is necessary because it is correlated with the value of glycamic index. Resistant starch content was determined by enzymatic process through glucooxydase method. RS content from four kinds of sago noodle ranged between 7,55 - 9,45 mg/g substances. Pancasan sago noodle showed the highest RS content, and this was further used to analysis the glycemix index.The glycemic index was determined based on ratio of area under blood glucose curve which represent total carbohydrate available from the 50 g glucose to the area under blood glucose curve which represent the glucose content after consumption of 50 gram glucose. The tested used seven health volunteers and resulted in glycemix index about 28. This level was considered low affect the blood glucose consuming. The sago noodle therefore the noodle can be constued by diebetes people Key words : resistant starch, glycemix index, sago noodle